Intimate Cyber Connectivity within Matrimony: A Comparative Jurisprudential Analysis of Electronic Sexual Relations among Spouses - Mohammed, Hossameldeen Khalil Farag; Jindiya, Nur Ahmad (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2024)
Research Objectives: This study explores electronic sex, or "e-sex," among couples, focusing on its various forms, types, motivations, justifications from the participants, and the associated risks. Research Method: The research utilizes a descriptive, analytical, and deductive approach to examine this contemporary phenomenon within the framework of Sharia law. Results: The study concludes that the practice of electronic sex between spouses is fundamentally prohibited due to the inherent dangers and ethical issues that contradict the core objectives of Sharia. Findings and Implications: The findings suggest that permission for such practices is granted only in specific cases and under strict supervision. This implies that exceptions can be made, but they must adhere to strict parameters. Conclusion: The primary purpose of marriage in Sharia law is to foster deep enjoyment between spouses. However, contemporary practices like electronic sex generally violate Sharia principles unless strictly controlled under necessary conditions. Contribution: This research enhances Sharia jurisprudence by examining new forms of marital relationships that have emerged during the contemporary information revolution, thereby providing legal guidance on issues previously unaddressed within Islamic law. Limitations and Suggestions: The study acknowledges that failure to adhere to the required controls necessitates consideration of the alternative solutions proposed. It also suggests further exploration of these alternatives and their implementation within a Sharia-compliant framework.